2014
DOI: 10.17221/890/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mineral fertilization impact on chemical and microbiological properties of soil and Miscanthus × giganteus yield

Abstract: This experimental work was undertaken to assess the effect of various fertilization regimes (CaNPK, NPK, CaPK, CaPN, CaKN and Ca) and different soil properties on growth and yield of Miscanthus plants and to check the impact of this plant on soil microbial characteristics. Field experiment was set up in 2003 on a long-term fertilization experiment, which had been established since 1923. Miscanthus giganteus response to high soil acidity and deficiency of N, P and K was investigated. Some physico-chemical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Inorganic fertilizer is often recommended to increase yields of biofuel crops on marginal lands (Tulbure et al, 2012). While nitrogen (N) fertilization has been shown to increase yields of switchgrass (Sanderson & Reed, 2000;Heaton et al, 2004) and miscanthus (Arundale et al, 2014b;Stepien et al, 2014), the use of synthetic N fertilizers for bioenergy crop production comes with economic costs to growers ($37 ha À1 estimated by Hallam et al, 2001), and does not always deliver higher yields (e.g., Dierking et al, 2016;Duran et al, 2016). Use of synthetic fertilizers also can compromise the climate benefits of planting perennial cellulosic biofeedstocks by increasing nitrate leaching and nitrous oxide emissions (Ruan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic fertilizer is often recommended to increase yields of biofuel crops on marginal lands (Tulbure et al, 2012). While nitrogen (N) fertilization has been shown to increase yields of switchgrass (Sanderson & Reed, 2000;Heaton et al, 2004) and miscanthus (Arundale et al, 2014b;Stepien et al, 2014), the use of synthetic N fertilizers for bioenergy crop production comes with economic costs to growers ($37 ha À1 estimated by Hallam et al, 2001), and does not always deliver higher yields (e.g., Dierking et al, 2016;Duran et al, 2016). Use of synthetic fertilizers also can compromise the climate benefits of planting perennial cellulosic biofeedstocks by increasing nitrate leaching and nitrous oxide emissions (Ruan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some successful efforts have been made to substitute excessive application of mineral fertilizers with natural substances and so to minimize the adverse effects of contamination (Javaid 2006, Stępień et al 2014. One of these efforts was selection of beneficial soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Miscanthus (Miscanthus × giganteus) has been documented to be particularly well suited to the temperate regions (Köppen Climate Classification System: Cfa, Cfb, Dfa, Dfb) of the United States (Kottek et al, 2006;Lee et al, 2014) and Europe, with recent reports proposing an expanded area of potential production based on current climatic conditions and genetics (Clifton-Brown et al, 2017). Reports from both the United States and Europe have demonstrated that M. × giganteus responds to N fertilization, but suggest that fertilization strategies should be tailored to specific site and within-site conditions (Arundale et al, 2013b;Stępień et al, 2014;Yost et al, 2017), including the possibility that N fertilization may increase the mobility of heavy metal contaminants in the soil (Pogrzeba et al, 2017). Lee et al (2014) summarized results from several miscanthus trials and reported dry biomass yields of 6 to 30 Mg ha -1 , with the least production from secondyr stands in the southeastern United States and the greatest from 3-to 5-yr stands in central and southern Illinois.…”
mentioning
confidence: 99%